Assessing Maturity level in game developing and publishing Organization - Pavlov, Evgenii (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Today organizations have to improve constantly service quality and performance to stay competitive. Since the 1970s, maturity models have been recognised as important improvement tools for organisations. Maturity models are a sequence of growth stages that illustrate the potential upward development or performance of organizations during the period of time. These models contribute to identifying capability levels of organizations, possible process improvements and help to track organizational maturity levels. Applying a maturity model forces organizations to commit to a number of instrumental procedures and assessments. Getting the maturity model accreditation/assessment can be a significant advantage for the companies. It can help to increase the quality of products and services, improve the performance of companies by enhancing work procedures. It can contribute in acquiring new clients as a maturity model appraisal serves as a sign of quality for new customers. However, one should always remember that maturity models show the growth stages of organization lifecycle and should be considered more as guidelines and tools to identify areas for possible improvement The aims of this study were to examine the current state of maturity models, chose the appropriate maturity model and apply it in the practical setting of the SME. In this study, we have examined the current trends of scientific literature in regards to maturity models. We have chosen, examined and compared four maturity models relevant to the research in terms of model adoption in an SME. During the empirical part, we have gathered and analyzed the company and management requirements for the purpose of maturity model implementation. Then based on the managements and company requirements we have selected the model for the practical application. Finally, we have applied the selected maturity model and assessed the maturity level of the organization.